2017
DOI: 10.1177/2309499016684723
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of extracorporeal shock wave therapy in snapping scapula

Abstract: Background: Bursitis of the snapping scapula is commonly a misdiagnosed problem. Extracorporeal shockwave therapy (ESWT) has been used successfully in the treatment of many chronic inflammatory conditions. The aim of this study was to assess and compare the effectiveness of ESWT in the treatment of scapulothoracic bursitis with the outcome of corticosteroid injection. Methods: Using the randomized controlled trials 43 patients with scapulothoracic bursitis were divided into two groups. Group 1 (n ¼ 22) receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“… 24 , 50 In this review, 4 studies (2 CSI and 2 ESWT therapy) found improved VAS scores from a mean of 7.7 ± 0.5 pretreatment to 2.4 ± 0.6 at the latest follow-up, which is comparable to the the 5 operative management studies reporting VAS improvement postoperatively, from a mean of 6.9 ± 0.7 to a mean of 1.9 ± 0.9. 1 , 2 , 7 , 8 , 13 , 23 , 35 , 41 , 47 Notably, this improvement in VAS is greater than the MCID of 3 for both groups. Only 1 comparative study was identified between open superomedial scapular resection to nonoperative management and no significant difference was found between groups in the low-power study.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“… 24 , 50 In this review, 4 studies (2 CSI and 2 ESWT therapy) found improved VAS scores from a mean of 7.7 ± 0.5 pretreatment to 2.4 ± 0.6 at the latest follow-up, which is comparable to the the 5 operative management studies reporting VAS improvement postoperatively, from a mean of 6.9 ± 0.7 to a mean of 1.9 ± 0.9. 1 , 2 , 7 , 8 , 13 , 23 , 35 , 41 , 47 Notably, this improvement in VAS is greater than the MCID of 3 for both groups. Only 1 comparative study was identified between open superomedial scapular resection to nonoperative management and no significant difference was found between groups in the low-power study.…”
Section: Discussionmentioning
confidence: 82%
“…Nonoperative treatment for SSS was analyzed in 8 studies (249 patients), as shown in Appendix Table 4 (available online) , with a mean age of 37.3 years and a mean follow-up of 5.9 months (range, 2.5-12 months). Visual analogue scale (VAS) pain scores were reported by 4 studies (2 investigated the use of ESWT, and 2 reported on CSI) 1 , 2 , 7 , 8 and improved from a mean of 7.7 ± 0.5 pretreatment to 2.4 ± 0.6 at the latest follow-up. While the minimal clinically important difference (MCID) was not reported by the aforementioned studies, the MCID for VAS has been previously reported to be 3, resulting in clinically significant reported pain reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroid injections (CSI) have also proven to be effective as an initial nonoperative treatment, which can be particularly useful as a diagnostic tool differentiating between scapular superomedial angle pathology and scapulothoracic bursitis in patients with superomedial angle pain (20). Extracorporeal shockwave therapy (ESWT) is another nonoperative modality, which has been successfully used in the treatment of snapping scapula bursitis (21). Both ESWT and CSI can be utilized as adjuncts to the rehabilitation program (21).…”
Section: Managementmentioning
confidence: 99%
“…Acar et al have recently described an Extracorporeal shockwave therapy (ESWT) with good outcome results in treatment of scapulothoracic syndrome [ 7 ]. Open or arthroscopic scapulothoracic surgical treatment is an option when non-operative modalities have failed.…”
Section: Introductionmentioning
confidence: 99%